2002
DOI: 10.1890/0012-9658(2002)083[2056:ddrobm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Density-Dependent Regulation of Body Mass and Condition in Badgers (Meles Meles) From Wytham Woods

Abstract: Body mass and an index of condition for badgers (Meles meles) in a highdensity population (Wytham Woods, UK) were examined between 1990 and 1997 and compared with the size of the groups with which individuals were associated. Both body mass and condition decreased as centered group size increased. Fecundity also declined with increasing centered group size. Female badgers exhibited the greatest effects of densitydependent constraints on body mass and condition in autumn, whereas for males the effect was most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 18 publications
0
43
0
Order By: Relevance
“…2000); demographic modelling would be needed to determine whether such mortality would be sufficient to suppress group size. Since females in smaller groups experience higher fecundity (Woodroffe & Macdonald 1995; Macdonald et al . 2002) and potentially higher cub survival (Woodroffe & Macdonald 2000) than females in larger groups, increased recruitment might compensate for elevated mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2000); demographic modelling would be needed to determine whether such mortality would be sufficient to suppress group size. Since females in smaller groups experience higher fecundity (Woodroffe & Macdonald 1995; Macdonald et al . 2002) and potentially higher cub survival (Woodroffe & Macdonald 2000) than females in larger groups, increased recruitment might compensate for elevated mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of group size on M. bovis infection could operate through susceptibility as well as through exposure. Badgers in larger social groups have lower body weights (Rogers, Cheeseman & Langton 1997; Macdonald et al . 2002), suggesting that they may be nutritionally stressed and therefore potentially susceptible to infection (Dai, Phalen & McMurray 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A specific change in the regulation of group sizes during the study period has been suggested [7,54,59] which may also have introduced noise into the data. Finally, it must be remembered that a lack of strong relationships in some cases may be because we can only approximate the total sum of earthworm availability.…”
Section: Discussionmentioning
confidence: 99%
“…Adult badger group sizes were estimated from trapping studies conducted since 1974 [7,11,21,39,54,59,71,81]. Where possible, we analysed data from all years in which it was collected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation